Genomic Analysis of SXT/R391 Integrative Conjugative Elements From Proteus mirabilis Isolated in Brazil - Sato, Juliana L.; Fonseca, Marina R. B.; Cerdeira, Louise T.; Tognim, Maria C. B.; Sincero, Thais C. M.; Noronha do Amaral, Mario C.; Lincopan, Nilton; Galhardo, Rodrigo S. (Frontiers in Microbiology, 2020)
Integrative conjugative elements (ICEs) are widespread in many bacterial species, often carrying antibiotic resistance determinants. In the present work, we screened a collection of Proteus mirabilis clinical isolates for the presence of type 1 SXT/R391 ICEs. Among the 76 isolates analyzed, 5 of them carry such elements. The complete sequences of these elements were obtained. One of the isolates carried the CMY-2 beta-lactamase gene in a transposon and is nearly identical to the element ICEPmiJpn1 previously described in Japan, and later shown to be present in other parts of the world, indicating global spread of this element. Nevertheless, the Brazilian isolate carrying ICEPmiJpn1 is not clonally related to the other lineages carrying the same element around the world. The other ICEs identified in this work do not carry known antibiotic resistance markers and are diverse in variable gene content and size, suggesting that these elements may be responsible for the acquisition of other advantageous traits by bacteria. Some sequences carried by these elements in Brazilian strains were not previously found in other SXT/R391 variants.